Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Kendaraan Bermotor - Furi, Ayunis Destia; Prima, Argo Putra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Motor vehicle tax is one of the revenues that contribute greatly to economic growth in a country that is collected on the ownership of motorized vehicles. Although the number of motorized vehicles increases every year, in reality there are still many people who do not comply with the obligation to pay taxes. Taxpayer compliance is an important aspect in the government's efforts to increase local revenue. The purpose of this study is to determine taxpayer compliance in Batam City, as well as the impact of taxpayer awareness, quality and sanctions on taxpayer compliance. This research uses a descriptive type quantitative approach. The random sampling method is used by researchers to take samples by distributing questionnaires to the people of Batam City who own motorized vehicles. There are 100 respondents who have been determined by researchers based on calculations using the slovin formula using multiple linear regression analysis techniques. The results of this study indicate that awareness and service quality have no significant effect on taxpayer compliance, while sanctions have a significant effect on taxpayer compliance.